Modern trends of the psychology sphere development in the optics of vitacultural methodology - Furman, Anatoliy V. (Psyhology & society, 2021)
The content of the program research is the latest material developed in recent years and announced on June 10, 2021 at the beginning of the Fifteenth meeting of the author’s scientific school. Its meaningfully-semantic mosaic is reflexively organized around two interdependent worldview concenters. The first comprehensively argues the nation-building orientation of collective thought-activity and vitacultural achievements of the representatives of this school during almost three decades of its modern history. Essentially, it is talked that a balanced usage of refined native language (perfect texts) and live speech (productive communication), symbolic means and graphic images, which in localized oases of artificial actualization of higher mental and spiritual values affirm the true Ukrainian heritage - the center of nourishing, covital and at the same time responsible national spirit. The second worldview concenter concerns radically to a broader, more meaningful and ontologically more adequate and covitally comprehensive understanding of psychology as a ubiquitous sphere of conscious human life activity. Against the background of the fact that psychology today is developing extensively on a civilized scale, ie within a purely scientific approach, continuously multiplying its own subjects in the general context of natural phenomena and appropriate methods of implementing various types of scientific rationality, it is proposed to radically change the methodological toolkit of its comprehensible elaboration, namely to make different a system of coordinates and a set of expedient lenses-means to the semantic comprehension, interpretation and creation of this flowing intangible reality. In this analytical context, one global and four derived trends in the interpenetrating development of modern psychology in Ukraine and the world are singled out and reflected. The quintessence of the global tendency is its intensive, heuristic way of progress into the boundless spherical horizons of actual human existence in the existential current of psycho-spiritual practice of persons, groups, societies as ontically rooted, universal, original sphere of thought-activity and its development as a special worldview, covital experience of everyday life and even lifestyle. The idea of such an alternative development belongs to G.P. Shchedrovitsky (1980), while its implementation has been carried out by us in the last decade in two basic aspects: a) within the application of the latest methodological optics – cyclical-deed approach to understanding psychology as a sphere of interpenetrating spheres of consciousness and activity, thinking and doing and b) in format of development, testing and implementation into the space of modern HEI (higher education institution) the author’s program in the discipline “Psychology as a sphere of thought-activity”, designed for professional training of applicants of the third (Doctor of Philosophy) level of training in the specialty 053 Psychology. As a result, for the first time situational, motivational, deed-action and post-action strategems of perfect thought-activity which substantiate the methodological organization of the psychology sphere are argued and described in detail. At the same time, the following important tendencies in the developmental course of psychology as anthropological science are highlighted: 1) a significant expansion of its subject field horizontally and vertically of new settings, including the full-fledged emergence of theoretical psychology; 2) the transition of research strategies and procedures from classical and non-classical ideals-types of scientific rationality to post-non-classical; 3) enrichment and disciplinary affirmation of canonical psychology and psychosophy of academician Volodymyr Romenets; 4) development of metamethodological means and tools for understanding-cognition-creation of metaphysical by ontological definition of images-substances-essences (thinking, freedom, creativity, faith, love, spirituality, etc.), firstly, creation of the most perfect methodological optics of meaningful comprehension of metatheoretical mosaic of life consciousness.